POTENTIAL ANTIVIRAL OF CATECHINS AND THEIR DERIVATIVES TO INHIBIT SARS-COV-2 RECEPTORS OF M pro PROTEIN AND SPIKE GLYCOPROTEIN IN COVID-19 THROUGH THE IN SILICO APPROACH - Frengki, Frengki; Putra, Deddi Prima; Wahyuni, Fatma Sri; Khambri, Daan; Vanda, Henni; Sofia, Vivi (Jurnal Kedokteran Hewan, 2020)
Catechin and their derivatives have been studied to have antiviral potential against COVID-19 through in silico method pharmacokinetics screening and molecular docking. Pharmacokinetics and toxicity profiles were obtained through the ADMETSAR server and SwissADME server. Then proceed with the prediction of affinity through the method molecular docking using the software application MOE 2007.09. The testmaterial is in the form of a 3D catechin structure and its derivatives as well as several control ligands downloaded via Pubmed. While templatethe Receptor M pro protein and the Spike glycoprotein are downloaded from pdb.org (PDB ID: 6LU7 and 6LXT). The pharmacokinetic profile of catechins is relatively better than all control ligands with the lowest toxicity. Molecular docking results also show that catechins and theirderivatives have a stronger affinity than control ligands. This research proves that catechin has antiviral potential through inhibition of Mpro protein and Spike glycoprotein COVID-19 virus.